2001
DOI: 10.1038/35091146
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative silencing elements in var genes

Abstract: Each Plasmodium falciparum malaria parasite carries about 50 var genes from a diverse family that encode variable adhesion proteins on the infected red blood cells of the host, but individual parasites single out just one var gene for expression and silence all the others. Here we show that this silencing is established during the DNA-synthesis phase (S phase) of the cell cycle and that it depends on the cooperative interaction between two elements in separate control regions of each var gene (the 5'-flanking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
166
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(174 citation statements)
references
References 10 publications
7
166
1
Order By: Relevance
“…These sequences are not found in blood stage promoters such as hrp3, msp1, var7b and knob-associated histidine rich protein (kahrp), suggesting that they are not involved in regulation of stage specificity in these promoters. Also, it has been reported that intronic regulatory elements regulate allelic expression in centromeric var7b genes [15,36]. Similarly, hrp3 5' end sequence contains an intron located 13 bp upstream of the ATG initiation codon [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These sequences are not found in blood stage promoters such as hrp3, msp1, var7b and knob-associated histidine rich protein (kahrp), suggesting that they are not involved in regulation of stage specificity in these promoters. Also, it has been reported that intronic regulatory elements regulate allelic expression in centromeric var7b genes [15,36]. Similarly, hrp3 5' end sequence contains an intron located 13 bp upstream of the ATG initiation codon [27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, early studies of the regulation of glycophorin binding protein 130 (gbp130) showed that the loss of trophozoite stage specificity was correlated with rearrangement of the chromatin structure on the plasmid copy [12]. In contrast, P. falciparum stage specific promoters such as histidine-rich protein-3 (hrp3) [25], PfEMP1 (var) [15] and P. berghei apical membrane antigen-1 promoter (Pbama1) [32] used to drive reporter gene expression on plasmids, maintained a strict developmental regulation despite the change in location. Together, these results indicate that regulatory mechanisms in the parasite might not be entirely dependent on chromosomal location.…”
Section: Location Of the Hrp3 Promoter On An Episome Did Not Affect Tmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not clear whether the var intron participates in regulating var mutually exclusive expression (46,47). Yet, the intron sequences apparently do harbor an insulator activity that antagonizes spreading of chromatin activation into neighboring loci (48).…”
Section: Cis-regulatory Elements That Control Var Expressionmentioning
confidence: 99%